Evaluation of a Group Cognitive Behavioral Dementia Caregiver Intervention in Latin America (2023)
Research has identified unique cultural factors contributing to dementia caregiving in Latin America but very few caregiver interventions have been systematically piloted and evaluated in this region. The purpose of this study was to examine the effective